First record of Phitacnemia picta (Drury, 1770) (Heteroptera: Coreidae), in the province of La Pampa, Argentina - Vilches, Juliana Y. (2014)
We report the first record of Phitacnemia picta capture (Drury, 1770) (Heteroptera: Coreidae) for the province of La Pampa. This species has economic importance attacking ornamental and fruit crops. This record brings the number of species of Heteroptera in the province.